Circuit Realization of Fractional Order Proportional Integral Controller for DC Motor - Kaur, Manpreet (My University, 2019)
Fractional order controllers are more flexible and perform in a better way than the integer order controllers i.e. simple Proportional Integral or Proportional Integral Derivative controller. The fractional order controller has the properties such as eliminating the steady state error, robustness towards the plant gain variations and also good disturbance rejection. In this work fractional order controller is designed for DC motor to control its speed and analogue realization of the controller is being performed. Mathematical model of DC motor is calculated. Stabilization of the system is done by calculating the parameters of the λPI controller. Then the values of the parameters that are obtained are been plotted in the (kp, ki) plane and the stability region for the λPI controller is observed. The resulted fractional order controller is designed with the help of Fractional Power Pole method. Circuit realization of fractional order Proportional Integral controller is done by approximating the rational function and it known as approximation method. Circuit testing of the controller is done through simulations. The proposed controller gives the desired results as the output tracks the set reference point.
ME
Keywords: Fractional Order Proportional Integral ( λ PI ); Proportional gain